2021
DOI: 10.3390/mi12020167
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Polycaprolactone Dissolving Microneedles Generated via the Thermal Melting Method for the Sustained Release of Capsaicin

Abstract: (1) Background: Dissolving microneedles (DMNs), a transdermal drug delivery system, have been developed to treat various diseases in a minimally invasive, painless manner. However, the currently available DMNs are based on burst release systems due to their hydrophilic backbone polymer. Although hydrophobic biodegradable polymers have been employed on DMNs for sustained release, dissolution in an organic solvent is required for fabrication of such DMNs. (2) Method: To overcome the aforementioned limitation, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…The base of needles was fabricated using PVP and PVA. 63 , 64 Recently, experiments demonstrated that Capsaicin can arrest cell cycle by eliciting cyclin-dependent kinase inhibitor P21 and inhibition of ERK1/2 signaling pathways, leading to decreased cell proliferation and promoted apoptosis via JNK activation. 64 Eum and co-workers successfully released Capsaicin using PCL needles for consecutive 15 days.…”
Section: Types Of Mn Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The base of needles was fabricated using PVP and PVA. 63 , 64 Recently, experiments demonstrated that Capsaicin can arrest cell cycle by eliciting cyclin-dependent kinase inhibitor P21 and inhibition of ERK1/2 signaling pathways, leading to decreased cell proliferation and promoted apoptosis via JNK activation. 64 Eum and co-workers successfully released Capsaicin using PCL needles for consecutive 15 days.…”
Section: Types Of Mn Devicesmentioning
confidence: 99%
“…Data showed that needles composed of biodegradable and biocompatible polymers like PCL can be used instead of hydrophobic polymers for trans-dermal delivery. 63 In an experiment conducted by Li and co-workers, a separable polyester kind patch was fabricated with a bubble technique. This technique supports immediate separation and effective insertion which is useful for contraceptive hormone delivery.…”
Section: Types Of Mn Devicesmentioning
confidence: 99%
“…This fabricating process involves multiple steps, such as master batch preparation, mold manufacturing, and plasticization of thermoplastic polymers, which is time-consuming. Moreover, polymer needs to be plasticized above its glass transition temperature [ 67 ], so maybe this method is not suitable for insulin, which is sensitive to heat. To avoid the high temperature for polymer dissolution in micro-molding method, researchers have extensively explored the water-soluble polymers in the fabrication of heat-sensitive drugs loaded dissolving MNs, including HA [ 68 ], γ-PGA, mixture of starch and gelatin [ 69 ], and mixture of fish gelatin and sucrose [ 70 ].…”
Section: Mns Used For Insulin Transdermal Deliverymentioning
confidence: 99%
“…Because the dissolution characteristics of polymer-containing DMNs are critical to controlling the drug release profile, the selection of a matrix polymer suitable for a required duration for medication is critical in the fabrication of DMNs [ 2 ]. Therefore, hydrophobic polymers such as poly(lactic-co-glycolic acid) (PLGA) or polycaprolactone (PCL) have been widely used for DMN fabrication, to deliver long-acting therapeutics in a sustained manner [ 13 , 14 ]. A representative approach tested PLGA as a matrix polymer for DMNs, wherein various therapeutics such as methotrexate, levonorgestrel, or etonogestrel were encapsulated in PLGA DMNs [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because organic solvents might be harmful when they are incompletely evaporated, an additional process to remove any residual organic solvent is necessary in the case of hydrophobic polymer-based DMNs [ 22 ]. To overcome this limitation, a recent study used heat-melted PCL rather than the dissolved form in organic solvents to fabricate DMNs for sustained capsaicin release [ 13 ]. Although not using the residual organic solvent certifies safety, controlling the desired drug release profile while using PCL that has sufficient mechanical strength for skin piercing when used in a DMN might be difficult, because the mechanical strength of PCL varies depending on its molecular weight [ 23 ].…”
Section: Introductionmentioning
confidence: 99%